The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0042905
|View full text |Cite
|
Sign up to set email alerts
|

Transformation with Oligonucleotides Creating Clustered Changes in the Yeast Genome

Abstract: We have studied single-strand oligonucleotide (oligo) transformation of yeast by using 40-nt long oligos that create multiple base changes to the yeast genome spread throughout the length of the oligos, making it possible to measure the portions of an oligo that are incorporated during transformation. Although the transformation process is greatly inhibited by DNA mismatch repair (MMR), the pattern of incorporation is essentially the same in the presence or absence of MMR, whether the oligo anneals to the lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 39 publications
(67 reference statements)
1
24
0
Order By: Relevance
“…In order to use oligos to incorporate a segment of DNA, it was necessary to know the frequency of co-incorporation of nucleotides in a given oligo. Using oligos with markers spread throughout the length of the oligo (Oligo N, Figure 1), we determined that for an oligo of 40 nt in length, a central core of 10–15 nt was incorporated with a greater than 90% frequency [43]. Those results suggested that it was feasible to use oligos of that length for our experiments.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In order to use oligos to incorporate a segment of DNA, it was necessary to know the frequency of co-incorporation of nucleotides in a given oligo. Using oligos with markers spread throughout the length of the oligo (Oligo N, Figure 1), we determined that for an oligo of 40 nt in length, a central core of 10–15 nt was incorporated with a greater than 90% frequency [43]. Those results suggested that it was feasible to use oligos of that length for our experiments.…”
Section: Resultsmentioning
confidence: 93%
“…A potential problem was that the region surrounding the mutant base is highly conserved, constraining the location of any damaged base. We therefore created the mutant trp5-G148Cm gene (Figure 1) [43]. Because this mutant trp5-G148Cm gene is placed close to a dependable origin of replication, and is present in both orientations relative to the origin, we know which strand is replicated as leading and which as lagging and can reverse the replication strands by using a strain of opposite TRP5 orientation [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work (Rodriguez et al, 2012) implicated the Fen1-endonuclease in flap degradation at the 5′ end of ssODNs. We posited that this effect could be partially explained by truncated ssODNs arising from errors in DNA synthesis since ssODNs are synthesized 3′ to 5′.…”
Section: Resultsmentioning
confidence: 99%
“…We found that variability in strand bias in the examined loci was consistent between strains and could not be solely explained by transcriptional effects (Figure 4) , which lend further mechanistic support for lagging strand incorporation of oligos at the DNA replication fork. (15, 21, 22)…”
Section: Resultsmentioning
confidence: 99%